Safe community movement in Serbia. (7th October 2012) - Milankov, M; Radovanovic, M; Mitrovic, D
Abstract : Background: In Serbia Safe Community programme has started in 2004. With first activities NGO Safe Community and continue with activities National centre for injury prevention and safety promotion from Novi Sad. Aims: To improve quality of live and injury prevention. Methods: Health promotion activities—Cooperation with the police station and activities related to the traffic, activities related to the safety at home and in public places, education and prevention of injuries at workplaces and at sport activities. Results: There are a lot different activities like: Safe and healthy mother—Safe and healthy child; Parent as a role models; The school of parenthood; Places that are and places that aren't playgrounds; Call 92, 93, 94—emergency phone line; How to behave when alone at home; First aid; Introducing to persons whom we can ask for help on the street; The volunteer fire department offers fire safety courses to the municipalities. Activities for safe moving of the disabled persons and their inclusion, marking the side walks and lowering the edges of the sidewalks, reconstruction of the access and placing slopes; SOS phone line and education and trainings on violence prevention; Suicide prevention project- Before crossing the fence call and etc. Significance: Two designated Safe Communities, Municipality of Backi Petrovac (2008) and City of Novi Sad (2009) and Affiliate Safe Community Support Centre (2009), First regional South eastern Europe Safe Community Conference (2009), South Eastern Europe Safe Community Network (2009), Safe Kids Serbia (2012).